2012
DOI: 10.3340/jkns.2012.52.3.234
|View full text |Cite
|
Sign up to set email alerts
|

Recent Changes in Risk Factors of Chronic Subdural Hematoma

Abstract: ObjectiveChronic subdural hematoma (CSDH) is a typical disease that is encountered frequently in neurosurgical practice. The medications which could cause coagulopathies were known as one of the risk factors of CSDH, such as anticoagulants (ACs) and antiplatelet agents (APs). Recently, the number of patients who are treated with ACs/APs is increasing, especially in the elderly population. With widespread use of these drugs, there is a need to study the changes in risk factors of CSDH patients.MethodsWe retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 20 publications
1
44
2
2
Order By: Relevance
“…Numerous studies have assessed the risk factors for recurrence, with over 20 different factors identified, highlighting the complexity and heterogeneity of this condition [6,7,[12][13][14]20,22].…”
Section: Reoperation Caused By Recurrent Hematomasmentioning
confidence: 99%
“…Numerous studies have assessed the risk factors for recurrence, with over 20 different factors identified, highlighting the complexity and heterogeneity of this condition [6,7,[12][13][14]20,22].…”
Section: Reoperation Caused By Recurrent Hematomasmentioning
confidence: 99%
“…The incidence of chronic subdural hematoma (CSDH) related to drugs affecting hemostasis has increased up to 14% in recent years11,19). At the end of the 20th century those patients account ed only for 1.2% of all patients with CSDH15).…”
Section: Introductionmentioning
confidence: 99%
“…4,5,8 A cSDH is a slowly progressive collection of liquefied SDH arising in 50% to 80% after minor head trauma. 4,14,18 The time interval from trauma to onset of symptoms is often delayed. Known additional risk factors are antiplatelet or anticoagulant therapy, age, and brain atrophy.…”
mentioning
confidence: 99%